ARRANGEMENT OF SPHERICAL DISKS FOR FRONTAL HARROWS - A. F. Zhuk; K. A. Sokht (Сельскохозяйственные машины и технологии, 2018)
Disk-type spherical working tools are widely used in soil-cultivating machines, where they serve as an element base for combined units and disk harrows, including the multi-row ones with disks on individual racks. The tools are used in the implementation of traditional technologies based on reversible plowing, with surface tillage after late-harvested predecessors, for example, corn, sunflower, and also in NO-TIL technologies. (Research purpose) To determine the arrangement of working tools on the disk harrow frame, which reduces the required number of disks and improves the quality of soil cultivation. (Materials and methods) The authors have analyzed the arrangement of disk harrow working tools and determined their rational arrangement and mutual positions in the rows, which increases the tillage width between adjacent soil strips, thus improving the completeness of soil shearing and loosening over the entire operating width with simultaneous decreasing of the required number of disks. (Results and discussion) The authors have determined the interrelated arrangement of disks in their rows, aimed at improving soil shearing, so that the number of strips tilled into a ridge by adjacent disks increases. It has been shown that the arrangement of working tools of the consecutive row determined by the orientation of the adjacent disks of the previous row, allows to economize one working tool for every 400 mm of its operating width when shearing the soil all the way across the entire width of the disk harrow. (Conclusions) It has been established that when soil is tilled with a disk and moved toward the already processed adjacent strip, the technological width of the disk coverage increases due to the deformation of soil tearing and shearing. The authors have proposed the arrangement order of spherical disks and their mutual orientation, which improves the quality of soil cultivation, the completeness of soil shearing along the entire operating width, and leads to a reduction in the number of disks.